Autophagy Induced by Micheliolide Alleviates Acute Irradiation-Induced Intestinal Injury via Inhibition of the NLRP3 Inflammasome - Wu, Dong-ming; Li, Jing; Shen, Rong; Li, Jin; Yu, Ye; Li, Li; Deng, Shi-hua; Liu, Teng; Zhang, Ting; Xu, Ying; Wang, De-gui (Frontiers in Pharmacology, 2022)
Radiation-induced enteropathy (RIE) is one of the most common and fatal complications of abdominal radiotherapy, with no effective interventions available. Pyroptosis, a form of proinflammatory regulated cell death, was recently found to play a vital role in radiation-induced inflammation and may represent a novel therapeutic target for RIE. To investigate this, we found that micheliolide (MCL) exerted anti-radiation effects in vitro. Therefore, we investigated both the therapeutic effects of MCL in RIE and the possible mechanisms by which it may be therapeutic. We developed a mouse model of RIE by exposing C57BL/6J mice to abdominal irradiation. MCL treatment significantly ameliorated radiation-induced intestinal tissue damage, inflammatory cell infiltration, and proinflammatory cytokine release. In agreement with these observations, the beneficial effects of MCL treatment in RIE were abolished in Becn1+/- mice. Furthermore, super-resolution microscopy revealed a close association between NLR pyrin domain 3 and lysosome-associated membrane protein/ light chain 3-positive vesicles following MCL treatment, suggesting that MCL facilitates phagocytosis of the NLR pyrin domain 3 inflammasome. In summary, MCL-mediated induction of autophagy can ameliorate RIE by NLR pyrin domain 3 inflammasome degradation and identify MCL as a novel therapy for RIE.